1D Nanostructures: 1D SbSeI, SbSI, and SbSBr With High Stability and Novel Properties for Microelectronic, Optoelectronic, and Thermoelectric Applications (Adv. Theory Simul. 1/2018). Issue 1 (18th January 2018) - Peng, Bo; Xu, Ke; Zhang, Hao; Ning, Zeyu; Shao, Hezhu; Ni, Gang; Li, Jing; Zhu, Yongyuan; Zhu, Heyuan; Soukoulis, Costas M.
Abstract : In article number 1700005, Hao Zhang and co‐workers discover 1D SbSeI, SbSI and SbSBr with high stability and novel properties based on first principles calculations. Bulk V‐VI‐VII compounds are earth‐abundant, and isolating one chain from them can be experimentally feasible. The electronic, optoelectronic, mechanical and thermoelectric performances are significantly improved over their bulk counterparts. A new pathway to obtain 1D nanostructures with highly desired properties is demonstrated.